Physicochemical Features of Hydrocarbon Fluid Flow in Shale Rocks: Review on Adsorption and Diffusion - Desmond Batsa Dorjhie; Aliya Mukhametdinova; Timur Yunusov; Christoph Faist; Hleb Lenski; Alexey Cheremisin; Mikhail Spasennykh (Georesursy, 2024)
Reliable data on the relative permeability of low-permeability organic-rich shale reservoirs are essential for optimizing the development and operation of these fields by enhancing hydrodynamic models. Key challenges and limitations in studying complex reservoir systems include limited experimental data due to a shortage of core samples and the inapplicability of conventional laboratory methods for characterizing gas flow due to properties of these reservoirs (low porosity and permeability, high amount of organic matter including kerogen).Investigating the effects of ultra-low interfacial tension, sorption, and diffusion on fluid flow under simulated reservoir conditions is crucial. Despite the importance of these factors, mechanisms of sorption and diffusion of hydrocarbon gases in shale rocks are often overlooked in experimental and numerical research on recovery strategies.This review aims to provide a comprehensive understanding of gas adsorption and diffusion related mechanisms in tight shale rocks. Main findings includes assessment how various rock properties affect fluid behavior in nanoscale pores and identify critical areas for experimental analysis. By generalizing the review results, this work also highlights emerging research trends and address limitations in integrating adsorption and diffusion data for recovery, improving the accuracy of recoverable reserve estimates and reducing economic risks in unconventional reservoir development.